CORRELATION BETWEEN ENGLISH PROFICIENCY AND EFFECTIVE CLASSROOM COMMUNICATION IN SECONDARY SCHOOLS IN ENUGU STATE, NIGERIA - Segun, Godwin Lamidi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Effective classroom communication is an essential component of teaching and learning in Nigeria's educational ecosystem. Indeed, there is growing concern about declining classroom communication in the school context. This present study aimed to determine the correlation between English proficiency and effective classroom communication using a sample of secondary school students from the post-primary education system in Enugu State, Nigeria. Two hundred and forty-eight respondents (n=248) completed a self-report measure of English proficiency and classroom communication. A Pearson's product-moment correlation was performed to ascertain the correlation between English proficiency and classroom communication among secondary school students. The analyses revealed a statistically significant, moderate positive correlation between English proficiency and classroom communication, r (246) = .39, p < .001. Most importantly, the R2 indicated that English proficiency explained about 21.2% of the variation in classroom communication. The study concludes that English proficiency is a determinant of student-teacher classroom interaction. The practical implications are discussed.